Perbandingan Sistem Pertanggungjawaban Pidana Korporasi sebelum adanya Ruu KUHP pada Ruu KUHP dan Sistem dari Negara Belanda - Agung Susanto (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
In the new KUHP bill, we are different from the old KUHP because the old KUHP still uses the Societas delinquere non potest principle, which means that corporations (legal entities) cannot commit criminal acts and cannot be held criminally accountable either. However, along with the development of the era with the number of cases involving corporations as perpetrators of criminal acts, the Criminal Code that we currently use has been revised, with the National Criminal Code Bill. The change is located in Article 45 paragraph 1 of the Draft Criminal Code, which states that corporations are criminal subjects. This research is normative juridical research that uses a Comparative Approach and a Statute Approach. The legal materials used are primary legal materials and secondary legal materials. The results of this study are that the Draft Criminal Code and the Special Law have not regulated the criminal liability of corporations committed by the private sector. Where in the Netherlands these arrangements have been regulated in the Dutch Penal Code in Article 328ter paragraph (1) and Article 328ter paragraph (2).